Cholinergic Responses and Intrinsic Membrane Properties of Developing Thalamic Parafascicular Neurons - Ye, Meijun (American Physiological Society, 2009)
Parafascicular (Pf) neurons receive cholinergic input from the pedunculopontine nucleus (PPN), which is active during waking and REM sleep. There is a developmental decrease in REM sleep in humans between birth and puberty and 10–30 days in rat. Previous studies have established an increase in muscarinic and 5-HT1 serotonergic receptor–mediated inhibition and a transition from excitatory to inhibitory GABA(A) responses in the PPN during the developmental decrease in REM sleep. However, no studies have been conducted on the responses of Pf cells to the cholinergic input from the PPN during development, which is a major target of ascending cholinergic projections and may be an important mechanism for the generation of rhythmic oscillations in the cortex. Whole cell patch-clamp recordings were performed in 9- to 20-day-old rat Pf neurons in parasagittal slices, and responses to the cholinergic agonist carbachol (CAR) were determined. Three types of responses were identified: inhibitory (55.3%), excitatory (31.1%), and biphasic (fast inhibitory followed by slow excitatory, 6.8%), whereas 6.8% of cells showed no response. The proportion of CAR-inhibited Pf neurons increased with development. Experiments using cholinergic antagonists showed that M2 receptors mediated the inhibitory response, whereas excitatory modulation involved M1, nicotinic, and probably M3 or M5 receptors, and the biphasic response was caused by the activation of multiple types of muscarinic receptors. Compared with CAR-inhibited cells, CAR-excited Pf cells showed 1) a decreased membrane time constant, 2) higher density of hyperpolarization-activated channels (I(h)), 3) lower input resistance (R(in)), 4) lower action potential threshold, and 5) shorter half-width duration of action potentials. Some Pf cells exhibited spikelets, and all were excited by CAR. During development, we observed decreases in I(h) density, R(in), time constant, and action potential half-width. These results suggest that cholinergic modulation of Pf differentially affects separate populations, perhaps including electrically coupled cells. Pf cells tend to show decreased excitability and cholinergic activation during the developmental decrease in REM sleep.